Covalent bonding in NiO: Evidence from a combined STM, LSDA plus U and EELS study - Castell, M; Dudarev, S; Botton, G; Briggs, G; Sutton, A (1998)
We show STM images that display fourfold symmetry hole states around point defects on the NiO (001) surface that are a number of times larger than the unit cell. The observation of these spatially delocalised states demonstrates that a reasonable description of bonding in NiO must go beyond a simple ionic interaction. This is achieved through the implementation of the LSDA + U model in simulating EELS spectra of the oxygen K edge. By using this method an accurate value for the electron-electron interaction parameter U of 6.2 eV can be determined, and hybridisation between O 2p and Ni 3d orbitals can be seen which points to the existence of a significant covalent contribution to bonding in NiO.